Efektivitas Perangkat Pembelajaran Berbasis Keterampilan Proses untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SD Ditinjau dari Kemampuan Akademik - Yusuf, Mochamad (Penerbit STKIP PGRI Bangkalan, 2018)
The purpose of this research is to measure the effectiveness of learning tools based on process skills to improve critical thinking skills in terms of students academic ability. The population of the research was students of Al Kautsar Elementary School in Pasuruan class V grade with a sample of 90 students, divided into categories of upper academic skills students, middle-academic skills students, and lower academic skills students. The results show that the average increase in critical thinking skills is different in every academic skills of students. In the upper academic skills students showed an average yield of N-Gains of 0.8 with a high increase category. In midle academic skills students showed an average yield of N-Gains of 0.7 with moderate improvement category. In lower academic skills students show the average N-Gains 0,5 result with moderate improvement category. The skill-based learning process will be more effective in improving critical thinking skills when applied to students with upper academic skills. The conclusion that can be drawn from this research is skill-based learning tool process effectively improve students critical thinking skill. However, skills-based learning process more effectively can improve students critical thinking skills with upper academic skills.